The The Influence of Breastfeeding Education on the Effectiveness of Breastfeeding in the Bajoe Community Health Center Work Area, Bone Regency - Muchtar, Asrianti Safitri; Fatmasanti, A. Ulfa; Musni, Musni; Azniah, Azniah; Novianti, Ita (Newinera Publisher, 2024)
The effectiveness of the breastfeeding process is defined as an interactive process between mother and baby that results directly in the transfer of milk from the mother's breast to the baby, in a behavior that reflects the fulfillment of the needs of the mother and baby. This research was conducted in the Bajoe Community Health Center, Bone Regency, with a research time design starting from June-September 2020 which aims to determine the effect of breastfeeding education on the effectiveness of postpartum maternal breastfeeding. This research method uses a pre-experimental design approach with one group pre-post test design approach. In this study, before the intervention was given, a pre-test was given which aimed to assess the effectiveness of breastfeeding. After the intervention was given, a post-test was given with a total sample of 46 people. The sampling technique used total sampling. The data analysis used was univariate and bivariate analysis presented in the frequency distribution table. For statistical tests, the level of significance used was p <0.05. The analysis used to determine the effect of breastfeeding education on the effectiveness of breastfeeding was a paired statistical test with a nonparametric test, namely the Wilcoxon test. Based on the results of statistical tests, it was found that the p value was 0.001 <0.05, which means that there was a significant effect of breastfeeding education on the effectiveness of breastfeeding for postpartum mothers in the working area of ​​the Bajoe Community Health Center, Bone Regency.